2009
DOI: 10.1159/000231988
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Report regarding the Use of Selective Sorbents in Complex Cardiac Surgery Patients with Extensive Sepsis and Prolonged Intensive Care Stay

Abstract: Aims: The purpose of this publication is to evaluate the first experiences with the supplemental use of selective endotoxin adsorption cartridges in the treatment of critically ill patients complicated by severe sepsis after cardiac surgery. Methods: Thirteen patients with Gram-negative sepsis underwent the procedure of selective lipopolysaccharide (LPS) adsorption using Alteco adsorber (group I) or Toraymyxin™ columns (polymyxin-B-immobilized fiber) (group II). Results: This therapy positively influenced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 50 publications
(19 reference statements)
2
32
0
Order By: Relevance
“…Analogous effects are described in other papers on the use of haemoperfusion on PMX-immobilised cartridge [19,20], as well as those on the use of ultrapermeable membranes in the intensive care of sepsis [12,14,25]. A number of authors have reported positive changes in haemodynamics accompanied by a statistically significant reduction of the inotrope dosage [21,26].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Analogous effects are described in other papers on the use of haemoperfusion on PMX-immobilised cartridge [19,20], as well as those on the use of ultrapermeable membranes in the intensive care of sepsis [12,14,25]. A number of authors have reported positive changes in haemodynamics accompanied by a statistically significant reduction of the inotrope dosage [21,26].…”
Section: Discussionsupporting
confidence: 54%
“…Targeted LPS adsorption haemodialysis (HD) with high cut-off membranes (EMiC2) has been effective in patients with sepsis [11,12,15,18,19,20,21]. However, there are no current publications on the combined use of extracorporeal approaches for simultaneous endotoxin elimination and lowering of the peak concentrations of inflammatory mediators.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical experience with this device is scarce, and is limited mainly to case reports and case series. [32][33][34] In general, these case series report a shorter vasopressor infusion duration in adsorber-treated patients compared with controls. Only one underpowered RCT has been published by local investigators.…”
Section: Alteco Lipopolysaccharide Adsorbermentioning
confidence: 78%
“…The procedures of LPS-adsorption were conducted according to the previously described protocol [11,12], using a MultiFiltrate machine (Fresenius, Germany). Before selective haemoperfusion, the extracorporeal circuit was washed with 4,000 ml of 0.9% NaCl solution and then with 500 ml of physiological saline supplemented with 2,500 IU of heparin.…”
Section: Methodsmentioning
confidence: 99%